Isomorphism Framework with Scenario Planning in Installing Lembang Fault Earthquake Disaster Information Board Signs - Meilina Wulandari; Nadia Yovani (Universitas Pendidikan Ganesha, 2023)
Installing disaster signs and information boards in disaster-prone areas is one form of effort to improve disaster preparedness and mitigation through disaster education for people in disaster-prone areas. This study aims to analyze the form of DiMaggio and Powell Isomorphism in the installation of signs and information boards for the Lembang Fault earthquake disaster and provide recommendations for the installation of signs and disaster information boards at the West Bandung Regency Regional Disaster Management Agency (BPBD KBB). The consideration of case selection is based on the high Indonesia Disaster Risk Index (IRBI) in 2022 in West Bandung Regency, reaching 14.74 (high risk for earthquakes). The research methodology uses a descriptive qualitative approach with case studies on BPBD KBB as coordinators in disaster management in the regions. Data collection techniques involve literature study and in-depth interviews. The results showed that the installation of signs and information boards was influenced by normative coercive Isomorphism. The implications of this study include practical recommendations for improving strategies for installing signs and information boards to improve the effectiveness of disaster mitigation in the region.